2009
DOI: 10.1136/sti.2008.033043
|View full text |Cite
|
Sign up to set email alerts
|

Role of widows in the heterosexual transmission of HIV in Manicaland, Zimbabwe, 1998-2003

Abstract: Background: AIDS is the main driver of young widowhood in southern Africa. Methods: The demographic characteristics of widows, their reported risk behaviours and the prevalence of HIV were examined by analysing a longitudinal populationbased cohort of men and women aged 15-54 years in Manicaland, eastern Zimbabwe. The results from statistical analyses were used to construct a mathematical simulation model with the aim of estimating the contribution of widow behaviour to heterosexual HIV transmission. Results: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
44
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(46 citation statements)
references
References 24 publications
2
44
0
Order By: Relevance
“…Studies have also demonstrated that widowers are more likely to engage in high-risk sexual behavior after the death of their spouse and contribute to new HIV infections in the population. 15 …”
Section: Discussionmentioning
confidence: 99%
“…Studies have also demonstrated that widowers are more likely to engage in high-risk sexual behavior after the death of their spouse and contribute to new HIV infections in the population. 15 …”
Section: Discussionmentioning
confidence: 99%
“…The pattern of heterogeneity we observed was unanticipated given that female heads of household are often thought to be the most vulnerable to the effects of economic insecurity. In particular, widows are thought to bear the worst of the ‘‘entangled crisis’’ [50] of FI, poverty, and HIV/AIDS—they may be evicted from their land, deprived of their livelihood, and stigmatized if their husband died of HIV infection—resulting in widows being at a heightened risk for HIV acquisition, if not already infected [7, 51, 52]. If this were true among the women in our sample, we would have expected FI to be strongly associated with risk behavior and relationship power among female heads of household, contrary to what we observe.…”
Section: Discussionmentioning
confidence: 99%
“…In rural Zimbabwe, for example, Lopman et al (2009) find that an estimated 6%–17% of all new infections occur through the sexual activity of widows and widowers. Bongaarts (2007) argues that the search for a suitable spouse prior to marriage holds greater risk than does the marriage itself, a phenomenon akin to what Magruder (2010) has called marital ‘shopping,’ claimed to occur frequently enough to have generated and now sustain the epidemic in South Africa.…”
Section: Background and Settingmentioning
confidence: 99%